Road charging in the Czech Republic and EU and external costs of transport - Bína, Ladislav; Černý, Václav (Univerzita Pardubice, 2010)
In the paper the Czech toll system and its future are presented. E-toll Czech project: Facts and Figures (today) are included and the next steps in the process of developing microwave infrastructure are mentioned. In the event of possible system extension of the roads of the 1st, 2nd and 3rd class (ca 55,000 km), the satellite technology will be used. The feasibility of such a combination of these two technologies, microwave and satellite, is subject to the compatibility of both systems in terms of the control equipment. For the microwave toll system, economic analyses according to EU directives were prepared for the Czech Ministry of Transport. Special attention is paid to the problems of traffic congestion, noise and damage to the environment, on the basis of the "user pays" and "polluter pays" according to the Eurovignette Directive principles. A complete survey of the EU toll system is included in the list of information sources.
Keywords: toll system; microwave and satellite toll system; EU directive; Eurovignette Directive; economic analyses